PENGEMBANGAN MEDIA VIRTUAL BOOK PADA MATERI BENTUK MOLEKUL - Haris Munandar; Sabarni Sabarni; Cut Utari Lydia Fitri (Lantanida Journal, 2020)
Research on the development of virtual books on geometri molecular form materials at MAS Ulumuddin Lhokseumawe, was motivated by the limited use of instructional media in learning process. The learning media used are reading books and LKPD, chemistry learning is also often considered difficult because generally the geometry molecular material is abstract and requires high imagination to understand it. Virtual books are media with animation in the form of software that can be accessed or opened via computers and laptops. The media is equipped with covers, instructions user, concept maps, materials, 3D molecular shapes and quizzes. The purpose of this study was to determine the development of a virtual book on molecular form materials using the development research method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques are validation sheets and response questionnaires. Based on the results of validation I 83.2%, validator II 92.8% and validator III 89.6%, the average score of expert validators from the expert validation sheet is 88.53% with very good criteria of virtual book. Based on the data from the implementetion results involving 16 students as respondents, an average percentage of 92.18% was obtained, so it can be concluded that the students responses to the virtual book media were very interesting.